The first step: which is better, the children`s sprint (50m running) with shoes or without shoes? - from the viewpoint of 2 dimensional biomechanical motion analyze - Tazuke, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Many Japanese children say, " I can run faster without shoes than with shoes! ". Several teachers in the elementary school measured the time of the children`s 50m running with shoes and without shoes. About 2/3 children ran faster without shoes than with shoes. But there is no study about the mechanisms. The purpose of this study is to research the biomechanical reason as the fast step, if children can run faster without shoes than with shoes. Methods In the experiment 1 subjects were an 8-year-old girl, a 9-year-old boy, a 10-year-old girl, a 13-year-old girl, over 40 year-old man and woman. All subjects ran 50m with shoes, the time of the each 10m was measured, and the running velocity of the each 10m was calculated. The running velocity between 20m and 30m of 5 subjects were fastest, the velocity between 30m and 40m of 1 subject was fastest. In the experiment 2 the high-speed video camera (made by NAC) was set up at the place where man can film at the 30m surrounding. All subjects ran for 50m 3 times with shoes and 3 times without shoes. The running motions of all subjects were filmed by the film rate of 1/250. The video films of the each fastest running with shoes and without shoes in all subjects were analyzed with motion analysis software, DYNAS by Shin Osaka Shokai Co. Ltd. Results Only children`s each running time without shoes were faster than that with shoes. 3 parameters, knee lift angle, knee angular velocity and swing-back velocity in the analyzed 29 parameters were increased in all children.